APPLICATION OF BED THICKNESS DISTRIBUTIONS IN TURBIDITE DEPOSITS OF LEMNOS ISLAND, NE GREECE - Maravelis, A.; Konstantopoulos, P.; Pantopoulos, G.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2007)
The submarine fan deposits in Lemnos Island, of the NE Greece provide a perfect opportunity to investigate the influence of processes such as erosion and bed amalgamation in the alternation of the shape of a power-law cumulative frequency distribution. The bed thickness distribution in two outcrops of late Eocene to early Oligocene turbidite deposits that correspond to different sub-environment, has been assessed statistically. Sediments of the outcrop 1 at the SE parts of the Lemnos Island interpreted as outer fan deposits and sediments of the outcrop 2 located at the NE parts of the island as inner fan deposits show both a good fit to the power-law, amplifying the hypothesis that departures from power-law statistics might be used as evidence of erosion and bed amalgamation. The main difference between these two outcrops is that the power law exponent decreases abruptly from outcrop 1 to outcrop 2, confirming with the aspect that the power law exponent can be considered as a good indicator for the available sedimentary space.